Effect of machining on the stress corrosion cracking behavior in boiling magnesium chloride solution of austenitic stainless steel. Issue 4 (10th November 2017) - Wu, Huanchun; Li, Chengtao; Fang, Kewei; Xue, Fei; Zhang, Guodong; Luo, Kunjie; Wang, Li
Abstract : The stress corrosion cracking (SCC) behaviors of Z3CN20.09M, 304L, and 316L austenitic stainless steels (SSs) after milling operation in boiling magnesium chloride solution were investigated by scanning electron microscopy (SEM), X‐ray diffraction, and 3D profilometer. The experimental results indicated that the roughness and residual stress increased with increasing feed rate of all specimens. The depth of deformation layer after milling operation reached about 150 µm shown as persistent slip bands (PSBs) were formed, leading to hardness enhanced obviously. After SCC tests in boiling magnesium chloride solution, the crack densities increased with increasing feed rate of the Z3CN20.09M SS specimens. However, the crack densities decreased as well as the intergranular (IG) cracking percentages increased with increasing feed rate of the 304L and 316L SS. Abstract : The crack densities increased with increasing feed rate of the Z3CN20.09M stainless steel (SS), while it reversed for the 304L and 316L SSs. It was worth noting that the length of single crack increased with increasing feed rate, although the crack numbers decreased for the 304L and 316L SSs. This should be attributed to the damage effect of the milling operations on the grain boundary during machining process.